(untitled) (Physical Education, Health and Social Sciences, 2025)
Biotechnology‍‌‍‍‌ research and development (R&D) projects have been identified as those that are prone to scientific uncertainties, with development cycles being drawn out, and technical interdependencies being intricate. Due to these aspects, effective leadership becomes a major factor in the success of such projects. This paper, based on transformational leadership theory, explores the effect of transformational leadership on project success in biotechnological R&D scenarios and also examines the roles of team cohesion and knowledge sharing as mediators and that of organizational resource readiness as a moderator. A quantitative and cross-sectional survey was undertaken targeting 327 leaders of biotechnology projects, senior scientists, and research managers from pharmaceutical companies, biomedical research institutes, and university laboratories. The outcome of the structural equation modeling (SEM) indicated that transformational leadership was a significant predictor of project success (β = .39, p < .001). Moreover, team cohesion (β = .21, p < .001) and knowledge sharing (β = .18, p < .001) were found to be partial mediators in this connection. The availability of organizational resources was a factor that influenced the relationship between transformational leadership and team cohesion, with the leadership effect being more potent when resources were ample (interaction β = .11, p = .013). The results of this research underscore the pivotal role of a transformational leader in the realization of outstanding scientific, technical, and commercial goals in biotechnology R&D. The paper contributes to the theoretical framework by providing the understanding of leadership in sectors characterized by high scientific uncertainty and also offers practical suggestions to biotech firms aiming at enhancing innovation and project ‍‌‍‍‌outcomes.